FEATURES OF FORMATING THE PROJECT COMPETENCE FOR FUTURE TEACHERS OF PRESCHOOL EDUCATION - Koshil, Oksana (Educological discourse, 2018)
One of the signs of the modern world is its technologizing, the widespread use of a technological approach in all spheres of life. Technology implies the effective use of all kinds of resources for optimal achievement of the set goals. Therefore, we believe that there is a need to prepare future educators for the project activity. In particular, the formation of project competence for future educators of pre-school establishments. On the basis of scientific analysis, project competence of future teachers is considered as an integrative integrity, knowledge, and skills that are necessary for the implementation of the project activity that causes the formation of quality professional competence of future specialists (the ability to apply design knowledge and skills in practice). The essence of the concepts of "competence", "competency", "design" has been described in the article. Effective ways of project competence development in future educators of pre-school establishments have been shown. Content-technological provision of project competence development for future educators during vocational training that effectively influences this process has been described in detail.